The Effectiveness of Gargling Binahong Decoction Solution and Betel Leaf Decoction Solution Againts Plaque Index (Study on Deaf Children at SDLB Karya Mulia Surabaya) - Isnanto Isnanto; Ajeng Nurzilullahningtiyas; Silvia Prasetyowati (International Journal of Advanced Health Science and Technology, 2023)
Deaf children are children who have hearing loss. They have limitations in terms of communication and lack of knowledge, which causes bad behavior. Behavior in maintaining poor dental and oral hygiene causes poor plaque index values in deaf children. The problem in this study is that the plaque index value of deaf students at SDLB Karya Mulia Surabaya is poor. Plaque control can be done by mechanical and chemical means. Chemical control of dental plaque can be done by gargling. Gargling using natural ingredients such as binahong leaves and betel leaves can help reduce plaque because they contain good antibacterial and antiseptic properties. The aim of this study was to determine the difference in the effectiveness of gargling a solution of decoction of binahong and betel leaves on the plaque index in deaf children at SDLB Karya Mulia Surabaya. The type of research used was a pre-experimental design with a pretest-posttest design, with 51 students as research subjects. Methods of data collection by way of observation. The data analysis technique uses the Independent Sample T-test. The results showed that the betel leaf decoction solution was more effective in reducing plaque index in deaf children at SDLB Karya Mulia Surabaya than the binahong leaf decoction solution.